A three-degree of freedom approach for the unilateral contact problem of plane cable trusses with tension-only harnesses. (June 2020) - Zurru, Marco
Abstract: The standard analysis of biconvex cable trusses is based on the finite elements method (FEM). Few analytical approaches have been presented and, to our knowledge, only one provides for a proper description of the slackening of tension-only harnesses. The present approach, based on the obvious observation that transversally unloaded - but axially tensioned - cables assume a rectilinear configuration, provides a detailed description of cable displacement and tension, in both cables and harnesses, and slackening of harnesses through a simple model, involving only three degrees of freedom. The model is based on piecewise parabolic and linear shape functions. The equilibrium is found via minimization of total potential energy. The results of this extremely simplified model are compared with those obtained by FEM and other analytical methods, on a previously studied, 60-meter span biconcave structure, demonstrating good agreement. The counterintuitive behaviour of the structure under different conditions of progressively increasing loads is investigated in detail.